2013
DOI: 10.1155/2013/840121
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Na+/H+-Exchanger (NHE-1, 2, and 4) Proteins and mRNA in Rodent’s Uterus under Sex Steroid Effect and at Different Phases of the Oestrous Cycle

Abstract: Precise uterine fluid pH regulation may involve the Na+/H+-exchanger (NHE). We hypothesized that NHE isoforms are differentially expressed under different sex steroid treatment and at different oestrous cycle phases which may explain the uterine fluid pH changes observed under these conditions. Method. Oestrous cycle phases of intact WKY rats were identified by vaginal smear. Another group of rats was ovariectomized and treated with 0.2 μg 17β-oestradiol (E), 4 mg progesterone (P), and E followed by P (E + P).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Our findings which indicate sex-steroids effect on uterine NHE-1, 2 and 4 expression were also consistent with the previous findings which reported that both estrogen and progesterone upregulated NHE-1 expression in the uterus (Gholami et al, 2013a).…”
Section: Fig 8 -Quantitative Analysis Of Fluorescence Signal Intensisupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings which indicate sex-steroids effect on uterine NHE-1, 2 and 4 expression were also consistent with the previous findings which reported that both estrogen and progesterone upregulated NHE-1 expression in the uterus (Gholami et al, 2013a).…”
Section: Fig 8 -Quantitative Analysis Of Fluorescence Signal Intensisupporting
confidence: 93%
“…Apically located NHE plays a role in mediating H + efflux which contributes towards decrease in luminal fluid pH. Expression of NHE-1, 2 and 4 have been reported in the uterus in mice (Wang et al, 2003) and has been shown to be regulated by ovarian steroids (Gholami et al, 2013a). Atrophy of female reproductive tract is an important complication of menopause attributed to estrogen deficiency (Bedell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The animals had a free access to soy-free diet (Gold Coin Pellet) and tab water ad libitum Based on treatment, the animals were distributed into different groups. Since serum 17 beta-estradiol concentrations vary markedly throughout the menstrual cycle, different doses of this hormone (0.2, 2, 20 and 50 g/kg), progesterone (4 mg/kg) (Gholami et al, 2013) were injected subcutaneously at the neck cuff with a 24-interval for 3 days consequently. Associated injections with the non-selective estrogen receptor (ER) antagonist ICI 182/780 25 mg/kg (Peng et al, 2010;Wakeling et al, 1991), a selective estrogen receptor beta antagonist (ER␤), 4-[2-phenyo-5,7-bis-(trifluoromrthyl)pyrazolo(1,5-a)pyrimidin-3-yl]phenol (PHTPP) 25 mg/kg, a selective estrogen receptor ␣ antagonist (1,3-bis-(4-hydroxyphenyl)-4-methyl-5-[4-(2-piperidinylethoxy)phenol]-1N-pyrazole dihydrochloride) MPP 25 mg/kg (Al-Nakkash, 2012), and mifepristone 7.5 mg/kg (Baan et al, 2005) were injected subcutaneously at the neck cuff 30 min before physiologic doses of estrogen and progesterone injection.…”
Section: Animal Preparationmentioning
confidence: 99%
“…A precise regulation of uterine fluid volume and Na þ concentration is important for successful reproductive events including sperm transport, embryo transport and implantation [1]. Any deviation from the normal fluid volume and Na þ concentration would cause adverse effects on embryo implantation [2].…”
Section: Introductionmentioning
confidence: 99%